Investigating solids, liquids, and gases with TOYS - Sarquis, Jerry L. (Middletown, Ohio : Terrific Science Press, 1997)
Presents twenty-four toy-based activities for use in middle-school classrooms that teach science lessons about matter and the changes it can undergo, providing opportunities for students to explore matter in its three states--solid, liquid, and gas.
"National Science Foundation.".
Includes bibliographical references and index.
Professional
Keywords: Change of state (Physics) -- Study and teaching (Secondary); Educational toys; Matter -- Properties -- Study and teaching (Secondary); Physics -- Study and teaching (Secondary) -- Methodology; Matter -- Study and teaching; Physics -- Study and teaching